Implementation of Coach McLungsSM into primary care using a cluster randomized stepped wedge trial design - Thomas Ludden; Katherine O’Hare; Lindsay Shade; Kelly Reeves; Charity G. Patterson; Hazel Tapp (BMC Medical Informatics and Decision Making, 2022)
Abstract Background Asthma is a prevalent chronic disease that is difficult to manage and associated with marked disparities in outcomes. One promising approach to addressing disparities is shared decision making (SDM), a method by which the patient and provider cooperatively make a decision about asthma care. SDM is associated with improved outcomes for patients; however, time constraints and staff availability are noted implementation barriers. Use of health information technology (IT) solutions may facilitate the utilization of SDM. Coach McLungsSM is a collaborative web-based application that involves pediatric patients, their caregivers, and providers in a personalized experience while gathering patient-reported data. Background logic provides decision support so both audiences can develop a well-informed treatment plan together. The goal of this study is to evaluate the implementation of the Coach McLungsSM intervention into primary care. Methods Implementation will be evaluated using a stepped wedge randomized control study design at 21 pediatric and family medicine practices within a large, integrated, nonprofit healthcare system. We will measure changes in emergency department visits, hospitalizations, and oral steroid use, which serve as surrogate measures for patient-centered asthma outcomes. We will use a generalized linear mixed models with logit link to test the hypothesis for the reduction in exacerbation rates specifying the fixed effects of intervention and time and random effects for practice and practice*time. This design achieves 84% power to detect the hypothesized effect size difference of 10% in overall exacerbation between control (40%) and intervention (30%) periods (two-sided, p = 0.05). Implementation will be guided using the Expert Recommendations for Implementing Change (ERIC), a compilation of implementation strategies, and evaluated using the CFIR (Consolidated Framework for Implementation Research) and RE-AIM (Reach Effectiveness, Adoption, Implementation, Maintenance). Discussion We anticipate that a tailored implementation of Coach McLungsSM across diverse primary care practices will lead to a decrease in emergency department visits, hospitalizations, and oral steroid use for patients in the intervention group as compared to the control condition. Trial Registration: Clincaltrials.gov, NCT05059210. Registered 28 September 2021, https://www.clinicaltrials.gov/ct2/show/NCT05059210